Hunter x hunter. Volume 7 - Togashi, Yoshihiro (Shonen Jump advanced manga., 2022)
Gon and Killua study the ways of Nen with master Wing at Heavens Arena. When Gon finally masters the use of Nen, he also passes the final portion of the Hunter Exam and Hisoka finally accepts his challenge.